The forest unseen : a year's watch in nature - Haskell, David George (Viking, 2012)
Biologist David Haskell uses a one-square-meter patch of old-growth Tennessee forest as a window onto the entire natural world. Visiting it almost daily for one year to trace nature's path through the seasons, he brings the forest and its inhabitants to vivid life. Each short chapter begins with a simple observation. From these, Haskell spins a web of biology and ecology, explaining the science that binds together the tiniest microbes and the largest mammals and describing the ecosystems that have cycled for thousands--sometimes millions--of years. --From publisher description.